ҚАШҚАДАРЁ ВИЛОЯТИ ШАРОИТИДА СОЯ ЕТИШТИРИШ ТАДҚИҚОТ НАТИЖАЛАРИНИ ИШЛАБ ЧИҚАРИШГА ЖОРИЙ ҚИЛИШ - Омонов, Ҳасан; Бекбўтаев, Ҳасан; Турдиев, Ё.; Мирзаев , Н.Ф. (Innovatsion texnologiyalar, 2022)
The article highlights the results of scientific research on improving the agricultural technology of cultivation of soybean varieties Amigo, Selekto-201, Tomaris-MAN-60, Oyjamol based on fertilizing with nitrogen fertilizers, carried out during 2018-2020. in conditions of light gray soils of Kashkadarya region